Method of making adhesive article by single facer coating
Patent Information
- Application Number
- CN202110304826.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-22
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-03-22
AI Technical Summary
此方法不适用于施涂工艺
[0019]本发明的单面上胶方法得到的粘合制品的初始粘结强度不小于3N/mm,最终粘结强度不小于4.5N/mm,初始耐热性测试的拉开距离不大于5mm,最终耐热性测试的拉开距离不大于40mm。本发明的方法得到的粘合制品具有良好的粘结强度和耐热性,制品在常温和高温下都具有粘结牢固、不易脱胶的特点。
Smart Images

Figure CN115109528B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing adhesive articles by applying adhesive to one side, the adhesive articles obtained therefrom, and the application of the adhesive articles in footwear production. Background Technology
[0002] The traditional bonding process for shoe materials in the footwear industry is a double-sided adhesive process, which involves applying adhesive to both the sole, upper, midsole, and outsole. Before applying the adhesive to the midsole, outsole, and upper, cleaning and a base coat are often required. For example, CN1235966C discloses a laminate comprising a foamed product layer and a polyolefin material layer, which uses a double-sided adhesive method for bonding. CN106316147A discloses an activator comprising a modified aminosilane and a solvent; the modified aminosilane is prepared by reacting an aminosilane compound with a silane modifier; the silane modifier is one or more of mono-glycidyl ether, di-glycidyl ether, and poly-glycidyl ether. The double-sided adhesive process is complex, inefficient, and labor-intensive, prompting the footwear industry to seek a simplified manufacturing process.
[0003] Single-sided gluing reduces the number of gluing steps, saves labor, improves production efficiency, and avoids adhesive contamination of the shoe upper, making it widely popular in the footwear industry. The challenge of single-sided gluing lies in finding suitable cleaning agents and adhesives.
[0004] Hot melt adhesives can be used in single-sided coating processes, but their application in the footwear industry is limited due to drawbacks such as poor initial performance and high equipment costs. The industry has been experimenting with water-based polyurethane dispersion adhesives for single-sided coating processes.
[0005] CN1098154C discloses a method for injection molding laminated articles, which involves applying a primer comprising an organic solvent and an ethylene or propylene polymer grafted thereon with unsaturated carboxylic acids or their anhydrides, esters, amides, imides or metal salts onto a substrate, and then injection molding the ethylene or propylene polymer onto the primer-coated substrate. This method is not applicable to coating processes.
[0006] CN107802056A discloses a method for manufacturing shoes using single-sided adhesive with powdered glue. The powdered glue used in this method includes common polyurethane resins and polyamide resins. The mechanical properties of shoe materials made by single-sided adhesive are significantly different from those of shoe materials made by double-sided adhesive.
[0007] CN108587495A describes a method for improving the performance of anaerobic adhesives by treating bonding surfaces with silane coupling agents, comprising the following steps: mixing and dissolving silane coupling agent, copper acetate, and ethanol in a mass ratio of 1:1:20 to obtain a pretreatment solution; uniformly applying the pretreatment solution to two bonding surfaces to obtain pretreated bonding surfaces; uniformly applying anaerobic adhesive to one of the pretreated bonding surfaces; and butt-fitting the two pretreated bonding surfaces together.
[0008] CN1095399A discloses a polyurethane melt binder comprising at least one polyurethane prepolymer obtained from at least one polyisocyanate, especially toluene diisocyanate and / or diphenylmethane diisocyanate, at least one polyalkylene glycol, especially polypropylene glycol, with a concentration of more than 10% by weight of the total melt binder, and at least one polyester glycol, preferably two polyester glycols with different glass transition temperatures, and additives such as resins, especially hydrocarbon resins, and stabilizers, particularly toluenesulfonyl isocyanate, as needed. Summary of the Invention
[0009] The purpose of this invention is to provide a method for preparing adhesive products using single-sided adhesive, the adhesive products prepared by this method, and their application in footwear production. The adhesive products prepared by the method of this invention exhibit good bonding strength and heat resistance.
[0010] A method for preparing adhesive articles by applying adhesive to a single surface according to the present invention includes the following steps:
[0011] a. Apply a cleaning agent to at least one surface of a first substrate, and allow it to dry.
[0012] The first substrate surface of the agent;
[0013] b. Apply an adhesive to at least one surface of a second substrate, and dry the surface with the adhesive applied.
[0014] The second substrate surface of the agent; and
[0015] c. Bring the surface of the first substrate treated in step a and the surface of the second substrate treated in step b into contact to obtain the adhesive article;
[0016] The cleaning agent comprises a polar solvent and a terminal aminosilane coupling agent; the polar solvent has a boiling point not exceeding 135°C and is isocyanate-free; the terminal aminosilane coupling agent conforms to the general formula YR. 1 -Si-(CH3) n X 3-n , where R 1It is an alkylene group having 1-20 carbon atoms, where n is 0 or 1, X is selected from -Cl, CH3O-, C2H5O-, (CH3)2CHO- and CH3OCH2CH2O-, and Y is selected from -NH2 and -NHR. 2 R 2 The cleaning agent is an alkyl group having 1-10 carbon atoms; the concentration of the cleaning agent is 0.2%-1.2%; the second substrate is pretreated with a treatment agent containing a halide and an organic solvent with a polarity greater than 2.4, and the concentration of the treatment agent is 1%-3%.
[0017] According to one aspect of the present invention, an adhesive article prepared by the method provided according to the present invention is provided.
[0018] According to another aspect of the invention, the use of the adhesive article provided by the invention in footwear production is provided.
[0019] The adhesive products obtained by the single-sided adhesive method of the present invention have an initial bond strength of not less than 3 N / mm, a final bond strength of not less than 4.5 N / mm, an initial heat resistance test pull-off distance of not more than 5 mm, and a final heat resistance test pull-off distance of not more than 40 mm. The adhesive products obtained by the method of the present invention have good bond strength and heat resistance, and the products are firmly bonded and not easily delaminated at both room temperature and high temperature. Detailed Implementation
[0020] This invention provides a method for preparing an adhesive article using a single-sided adhesive, comprising the following steps: a. applying a cleaning agent to at least one surface of a first substrate and drying the surface of the first substrate to which the cleaning agent was applied; b. applying an adhesive to at least one surface of a second substrate and drying the surface of the second substrate to which the adhesive was applied; and c. bringing the surface of the first substrate treated in step a and the surface of the second substrate treated in step b into contact to obtain the adhesive article; wherein the cleaning agent comprises a polar solvent and a terminal aminosilane coupling agent; the polar solvent has a boiling point not exceeding 135°C and isocyanate non-reactive; the terminal aminosilane coupling agent conforms to the general formula YR. 1 -Si-(CH3) n X 3-n , where R 1 It is an alkylene group having 1-20 carbon atoms, where n is 0 or 1, X is selected from -Cl, CH3O-, C2H5O-, (CH3)2CHO- and CH3OCH2CH2O-, and Y is selected from -NH2 and -NHR. 2 R 2The cleaning agent is an alkyl group having 1-10 carbon atoms; the concentration of the cleaning agent is 0.2%-1.2%; the second substrate is pretreated with a treatment agent comprising a halide and an organic solvent with a polarity greater than 2.4, and the concentration of the treatment agent is 1%-3%. The present invention also provides adhesive articles prepared by this method and their application in footwear production.
[0021] The use of "first" and "second" in the description of the first and second substrates of the present invention is merely for the convenience of describing the two substrates and is not intended to distinguish the order of the substrates.
[0022] The first substrate and the second substrate of the present invention may be the same or different.
[0023] Steps a and b are not sequential; they can be performed simultaneously, or step a can be performed first and then step b, or step b can be performed first and then step a.
[0024] The concentration of the treatment agent in this invention is calculated as (halide mass (g) / treatment agent mass (g)) × 100%.
[0025] The concentration of the cleaning agent of the present invention is calculated as (mass of terminal aminosilane coupling agent (g) / mass of cleaning agent (g)) × 100%.
[0026] The "isocyanate non-reactiveness" of this invention refers to the absence of Zerevitinov active hydrogen. The definition of Zerevitinov active hydrogen can be found in the 10th edition of the Rompp Chemical Dictionary, Georg Thieme Verlag Stuttgart, 1996. Generally, groups containing Zerevitinov active hydrogen include, but are not limited to, hydroxyl, amino, and thiol groups.
[0027] Cleaning agents
[0028] The concentration of the cleaning agent is preferably 0.3%-1.0%.
[0029] The amount of the terminal aminosilane coupling agent is preferably 0.2%-1.2% by weight, most preferably 0.3%-1.0% by weight, relative to the total weight of the cleaning agent.
[0030] The polar solvent of this invention refers to a solvent whose solvent molecules are polar molecules.
[0031] The boiling point of the polar solvent is preferably 35℃-135℃.
[0032] The polar solvent is preferably one or more of acetone, methyl ethyl ketone, ethyl acetate or butyl acetate, a mixture of butyl acetate and cyclohexane and methyl ethyl ketone, a mixture of methyl ethyl ketone and propylene glycol diacetate, or a mixture of butyl acetate and methyl ethyl ketone and propylene glycol methyl ether acetate.
[0033] The polar solvent is further preferably selected from methyl ethyl ketone (MEK), butyl acetate, a mixture of MEK and ethyl acetate, a mixture of MEK and butyl acetate, a mixture of MEK and propylene glycol diacetate, a mixture of acetone and butyl acetate, a mixture of ethyl acetate and butyl acetate, a mixture of ethyl acetate, butyl acetate and MEK, a mixture of butyl acetate, cyclohexane and MEK, and a mixture of butyl acetate, MEK and propylene glycol methyl ether acetate.
[0034] The preferred polar solvent is methyl ethyl ketone (MEK).
[0035] The R 2 Alkyl groups having 1-6 carbon atoms are preferred, and alkyl groups having 1-4 carbon atoms are most preferred.
[0036] The terminal aminosilane coupling agent is preferably one or more of the following: γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and bis-(γ-trimethoxysilylpropyl)amine.
[0037] The cleaning agent preferably contains methyl ethyl ketone and an amino-terminated silane coupling agent, and the cleaning agent concentration is 0.3%-1.0%.
[0038] The cleaning agent does not contain adhesives.
[0039] The polar solvent and the amino-terminated silane coupling agent in the cleaning agent can be stored separately or pre-mixed and present in solution form.
[0040] First substrate
[0041] The first substrate is one of those commonly used in the art, particularly materials suitable for use in shoe midsoles, uppers, and toes. The first substrate is preferably one or more of the following: polyurethane-based materials and polyvinyl chloride materials, with polyurethane-based synthetic leather being the most preferred.
[0042] adhesives
[0043] The adhesive may be a single-component adhesive, a two-component adhesive, or a three-component adhesive commonly used in the art.
[0044] The adhesive is preferably one or more of the following: solvent-based polyurethane, solvent-based polychloroprene rubber, waterborne polyurethane dispersion, waterborne polychloroprene rubber and hot melt adhesive polyurethane, more preferably waterborne polyurethane dispersion, and most preferably two-component waterborne polyurethane dispersion.
[0045] The two-component waterborne polyurethane dispersion preferably comprises a waterborne polyurethane dispersion and an isocyanate curing agent.
[0046] The aqueous polyurethane dispersion is preferably an anionic aqueous polyurethane dispersion.
[0047] The solid content of the aqueous polyurethane dispersion is preferably 40%-60% by weight, relative to the total weight of the aqueous polyurethane dispersion.
[0048] The isocyanate curing agent is preferably a water-dispersible isocyanate, and most preferably a trimer of an aliphatic isocyanate.
[0049] The isocyanate curing agent preferably meets at least one of the following characteristics:
[0050] The isocyanate group content is 15%-25% by weight, relative to the total weight of the isocyanate curing agent;
[0051] Viscosity of 2000 mPa·s-4000 mPa·s, according to DIN EN ISO 3219:1994-10 at 23°C and 10s -1 The MV-DIN rotor was selected for measurement at the shear rate.
[0052] Isocyanate functionality 2.8-3.5; and
[0053] Number average molecular weight: 200 g / mol - 2000 g / mol.
[0054] Second substrate
[0055] The second substrate is one of those commonly used in the art, especially rubber materials that can be used for shoe outsoles and midsoles.
[0056] The second substrate is preferably one or more of the following: natural rubber and synthetic rubber. The synthetic rubber is preferably one or more of the following: nitrile rubber, TPU, TPR, and polyvinyl chloride materials.
[0057] The second substrate is pretreated with a treatment agent before the adhesive is applied.
[0058] The organic solvent with a polarity greater than 2.4 in the treatment agent is preferably one or more of the following: ethyl acetate, butyl acetate, butanone, and acetone.
[0059] The preferred halide is trichloroisocyanuric acid.
[0060] The treatment agent preferably comprises trichloroisocyanuric acid and ethyl acetate, with a concentration of 1%-3%.
[0061] The pretreatment preferably involves applying the treatment agent to at least one surface of the second substrate and drying it.
[0062] The second substrate can also be sanded or cleaned before the adhesive is applied.
[0063] The polishing is used to improve the surface roughness of the substrate. The polishing can be mechanical polishing.
[0064] The cleaning process involves using a solvent to remove oil or dust from the surface of the substrate, and the solvent is one that is well known to those skilled in the art.
[0065] Application
[0066] The application may be performed by applying the cleaning agent or adhesive to the entire surface of the substrate or to one or more portions of the surface of the substrate.
[0067] The coating process can be brushing, dipping, spraying, roller coating, doctor blade coating, flow coating, pouring, printing, or transfer, with brushing, dipping, or spraying being preferred.
[0068] dry
[0069] The drying of the first substrate surface to which the cleaning agent has been applied and the drying of the second substrate surface to which the adhesive has been applied can refer to drying only the substrate surface, or it can refer to drying part or all of the substrate, including the substrate surface to which the cleaning agent or adhesive has been applied.
[0070] The drying process removes volatile components, which may be water.
[0071] The drying process preferably uses one or more of the following: infrared thermal radiation, near-infrared thermal radiation, microwave, and convection oven or spray dryer under elevated temperature conditions.
[0072] The drying temperature should not exceed the temperature limit at which the substrate deforms uncontrollably or suffers other damage.
[0073] touch
[0074] Preferably, before step c, the surface of the second substrate with the adhesive applied after step b is thermally activated at a temperature of 45°C-75°C.
[0075] The thermal activation can be oven activation or infrared activation.
[0076] The contact is preferably performed before the temperature of the second substrate surface drops below the adhesive's bonding temperature, and more preferably before the temperature of the second substrate surface is not lower than 60°C.
[0077] The first substrate was not treated with adhesive before it came into contact with the second substrate.
[0078] Adhesive products
[0079] The initial bonding strength of the adhesive product is preferably not less than 3 N / mm, and most preferably 3 N / mm-5.5 N / mm.
[0080] The final bonding strength of the adhesive product is preferably not less than 4.5 N / mm, and most preferably 4.5 N / mm-7.0 N / mm.
[0081] The initial heat resistance test of the adhesive product is preferably conducted at a pull-out distance of no more than 5 mm, and most preferably 1 mm to 5 mm.
[0082] The pull-out distance for the final heat resistance test of the adhesive product is preferably no more than 40 mm, and most preferably 0 mm-37 mm.
[0083] The adhesive product is preferably footwear. Attached Figure Description
[0084] The present invention will now be described and explained in more detail with reference to the accompanying drawings, wherein:
[0085] Figure 1 This is a schematic diagram of the sample bonding process.
[0086] Figure 2 This is a schematic diagram of the sample's heat resistance test.
[0087] Example
[0088] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any discrepancy between the definitions of terms in this specification and their commonly understood meaning by one of ordinary skill in the art to which this invention pertains, the definitions set forth herein shall prevail.
[0089] Unless otherwise stated, all numerical values for the amounts of expressed components, reaction conditions, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values that can be varied to obtain the desired performance.
[0090] The word “and / or” as used in this article refers to one or all of the elements mentioned.
[0091] The terms "include" and "contain" as used in this article cover both cases where only the mentioned elements exist and cases where other unmentioned elements exist in addition to the mentioned elements.
[0092] All percentages in this invention are weight percentages, unless otherwise stated.
[0093] All analytical measurements in this invention are performed at 23±2℃, unless otherwise stated.
[0094] Raw materials and reagents
[0095] Silquest A-1100: γ-aminopropyltrimethoxysilane, available from Momentive China Ltd.
[0096] Silquest A-1120: N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, available from Momentive China Ltd.
[0097] Silquest A-1170: Bis(γ-trimethoxysilylpropyl)amine, available from Momentive China Ltd.
[0098] Silquest A-1524: γ-(biuret)propyltrimethoxysilane, available from Momentive China Ltd.
[0099] Silquest A-link 25: γ-(isocyanate)propyltriethoxysilane, available from Momentive China Ltd.
[0100] Desmocoll 526: Polyurethane resin, available from Covestro Ltd.
[0101] Dispercoll U 54: An anionic aqueous polyurethane dispersion with a solids content of 50±1%, available from Covestro Ltd.
[0102] Polyester I: 1,4-Butanediol polyadipate diol, OH value = 50.
[0103] Polyester II: A polyester diol composed of 1,6-hexanediol, neopentyl glycol and adipic acid, with an OH value of 66.
[0104] H: 1,6-Hexamethylene diisocyanate, available from Covestro Ltd.
[0105] I: Isophorone diisocyanate, available from Covestro Ltd.
[0106] Dispercoll U58 / 1: Anionic aqueous polyurethane dispersion with a solids content of 50+1%, available from Covestro Ltd.
[0107] Desmodur XP 2802: 40% by weight solids, hydrophilic modified polycarbodiimide, melting point of solids 23.16℃, carbodiimide functional group content 1 mmol / g, number average molecular weight 1779, weight average molecular weight 3258, carbodiimide functional group functionality 4.5, available from Covestro.
[0108] Bayhydur XP 2655: An HDI-based aliphatic trimer with 20.8% NCO group content, a viscosity of approximately 3500 mPa·s (23°C), 100% solids content, isocyanate functionality of 3.2, and a number-average molecular weight of 700 g / mol. It is available from Covestro.
[0109] MEK: Methyl ethyl ketone, purchased from Yonghua Chemical Technology (Jiangsu) Co., Ltd.
[0110] Black rubber: The sole rubber made of nitrile rubber, which can be purchased from Dongguan Wantai Rubber Co., Ltd.
[0111] L-10: PU synthetic leather, available from Anhui Anli Synthetic Leather Co., Ltd.
[0112] L-27A: PU synthetic leather, available from Anhui Anli Synthetic Leather Co., Ltd.
[0113] L-35: PU synthetic leather, available from Anhui Anli Synthetic Leather Co., Ltd.
[0114] Borchigel L75N: Thickener, purchased from OMG.
[0115] Preparation of adhesive 1
[0116] Mix 99.2g of Dispercoll U58 / 1 and 0.8g of 25% Borchigel L75N until the viscosity is about 5000mPa·s. After stirring for 10 minutes, add 5g of Bayhydur XP 2655 and continue stirring for 10 minutes to obtain adhesive 1.
[0117] Preparation of adhesive 2
[0118] 450g of polyester I and 42.5g of polyester II were dehydrated at 110℃ and 100mbar for 1 hour, then 2.25g of 1,4-butanediol was added while the mixture was cooled with stirring. 37.84g of [unspecified substance] was added at 60℃. H, then add 25g 1. Stir the mixture at 80-90°C until an isocyanate content of 1.3% isocyanate is achieved. Dissolve the reaction mixture in 840g of acetone and cool to 50°C. Add a solution of 5.6g of sodium salt of N-(2-aminoethyl)-2-aminoethanesulfonic acid, 2.4g of diethanolamine, and 0.8g of hydroxyethyl ethylenediamine in 656g of water to the reaction mixture and stir vigorously for 30 minutes. Then add 510g of water to disperse the mixture, and subsequently distill off the acetone to obtain an aqueous polyurethane dispersion. Mix 100g of the above aqueous polyurethane urea dispersion with 2g of Desmodur XP2802 at 1000rpm for 10-15 minutes. Then add approximately 1g of Borchigel L75N with a solid content of 25% and mix until the viscosity is approximately 5000mPa·s. Stir for 10 minutes, then add 5g of Bayhydur XP 2655 and continue stirring for 10 minutes to obtain binder 2.
[0119] Substrates of the Examples and Comparative Examples
[0120] Mix the components of the cleaning agent according to the amounts shown in Table 1, and stir manually for 5-10 minutes to obtain the cleaning agent. Clean the surface of the PU synthetic leather (first substrate) (2 cm wide, 8 cm long) to be bonded with a fiber containing the cleaning agent, gently scrub several times, and then dry in an oven at 60°C for 3 minutes before use.
[0121] Clean the sanded black rubber (second substrate) surface (2 cm wide, 8 cm long) to be bonded with a fibrous cloth or yarn containing methyl ethyl ketone (MEK). Expose the cleaned black rubber surface in a fume hood until it is dry. Apply the treatment agents shown in Table 1 (treatment agent 1 contains trichloroisocyanuric acid and ethyl acetate, concentration 2%; treatment agent 2 contains Silquest A-1170 and MEK, concentration 1%) to the surface. Then dry in an oven at 60°C for 3 minutes. Finally, apply the adhesive shown in Table 1 to the black rubber surface with a fine brush, at a rate of 120 g / m². 2 (Wet). Finally, dry the black rubber surface coated with adhesive in a circulating air oven at 60°C until all moisture in the adhesive film is removed, and set aside for later use.
[0122] Bond strength test
[0123] The surface of the prepared black rubber is heated to 60°C, and then a flatbed press (China Rongtai) is used to quickly bond the black rubber to the prepared PU synthetic leather at a pressure of 4 bar. Figure 1 As shown, the sample of the adhesive product is obtained by holding it for 30 seconds.
[0124] According to DIN EN 1392, the bond strength of the samples was tested using a ZWICK BZ2.5 / TN1S tensile testing machine. The unbonded portions of the black rubber and PU synthetic leather were clamped in the upper and lower fixtures of the tensile testing machine. The test was conducted at a tensile rate of 100 mm / min and a tensile length of 50 mm, showing a 180° peel. The tensile force used at this point was recorded as the bond strength, and the results are listed in Table 1. The initial bond strength (tested 30 minutes after bonding) should be no less than 3 N / mm, and the final bond strength (tested 24 hours after bonding) should be no less than 4.5 N / mm. A higher bond strength indicates a stronger bond between the substrates and a more secure adhesion.
[0125] Heat resistance test
[0126] The surface of the prepared black rubber is heated to 60°C, and then a flatbed press (China Rongtai) is used to quickly bond the black rubber and the prepared PU synthetic leather together at a pressure of 4 bar. Figure 1 As shown, the sample of the adhesive product is obtained by holding it for 10 seconds.
[0127] Initial heat resistance test: The sample was placed at room temperature for 2 minutes, then a 500g weight was applied at 80℃ and maintained for 30 minutes. Figure 2 As shown in Table 1, the separation distance of the sample after being held at 80℃ for 30 minutes was recorded. If the coating could not be maintained for 30 minutes and completely separated, the time of complete separation was recorded. The results are shown in Table 1. The separation distance was measured with a ruler to determine the length of separation between the bonded parts of the sample. The longer the separation distance, the worse the heat resistance of the sample. Complete separation means that the bonded parts of the sample are completely separated, and the sample is considered to have failed the heat resistance test. The separation distance should not exceed 5 mm.
[0128] Final heat resistance test: The sample was placed at room temperature for 24 hours, then a 1000g weight was applied at 80℃ and maintained for 30 minutes. Figure 2 As shown in Table 1, the separation distance of the sample after being held at 80℃ for 30 minutes was recorded. If the coating could not be maintained for 30 minutes before completely separating, the time of complete separation was recorded. The results are shown in Table 1. The separation distance was measured with a ruler to indicate the length of separation between the bonded parts of the sample. The longer the separation distance, the worse the heat resistance of the sample. Complete separation means that the bonded parts of the sample are completely separated, and the sample is considered to have failed the heat resistance test. The separation distance should not exceed 40 mm.
[0129] Examples 1-9 and Comparative Examples 1-12
[0130] Table 1 lists the test results of the bonding strength and heat resistance of the treatment agents, cleaning agents, and adhesive samples of Examples 1-9 and Comparative Examples 1-12.
[0131] Table 1. Test results of the subdivided and bonded product samples of the Examples and Comparative Examples.
[0132]
[0133]
[0134] As can be seen from Examples 1-9, the adhesive products obtained by the single-sided adhesive method of the present invention have an initial adhesive strength of not less than 3 N / mm, a final adhesive strength of not less than 4.5 N / mm, an initial heat resistance test pull-out distance of not more than 5 mm, and a final heat resistance test pull-out distance of not more than 40 mm. The adhesive products obtained by the method of the present invention all have good adhesive strength and heat resistance.
[0135] As can be seen from Comparative Examples 1-3 and 1-7, when the cleaning agent concentration is 0.2%-1.2% and a suitable terminal aminosilane coupling agent is selected, the adhesive products obtained by the single-sided adhesive method have good bonding strength and heat resistance. In Comparative Example 1, the cleaning agent contained only methyl ethyl ketone (MEK). The adhesive products obtained by the method in Comparative Example 1 showed complete delamination within 5 minutes in the initial heat resistance test and within 9 minutes in the final heat resistance test, indicating poor heat resistance. In Comparative Example 2, the cleaning agent concentration was 0.1%. The adhesive products obtained by the method in Comparative Example 2 showed complete delamination within 12 minutes in the initial heat resistance test and within 18 minutes in the final heat resistance test, indicating poor heat resistance. In Comparative Example 3, the cleaning agent concentration was 1.5%. The adhesive products obtained by the method in Comparative Example 3 had an initial bond strength of 2.9 N / mm and a final bond strength of 3.9 N / mm, both below the required bond strength, indicating poor bond strength.
[0136] As can be seen from Comparative Examples 4-7, the cleaning agents of the comparative examples contain γ-(biuret)propyltrimethoxysilane or γ-(isocyanate)propyltriethoxysilane, and the adhesive products of the comparative examples cannot simultaneously achieve both adhesive strength and heat resistance.
[0137] The cleaning agent used in the single-sided adhesive method of Comparative Examples 8-9 is methyl ethyl ketone (MEK). Compared with the adhesive products of Examples 8-9 of the present invention, the adhesive products of the comparative examples have poor initial heat resistance and final heat resistance.
[0138] As can be seen from Comparative Examples 10-11, the cleaning agents of the comparative examples contain Desmocoll 526 or Dispercoll U 54, and the adhesive articles of the comparative examples have poor initial heat resistance and final heat resistance.
[0139] As can be seen from Comparative Example 12, when the treatment agent contains Silquest A-1170 and methyl ethyl ketone, the bonding strength and heat resistance of the product of the comparative example are poor.
[0140] It will be readily apparent to those skilled in the art that this invention is not limited to the specific details described above, and that it may be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments described should be considered illustrative rather than restrictive in any way, and the scope of the invention is indicated by the claims rather than the foregoing description; and thus any modifications that fall within the meaning and scope of the equivalents of the claims should be considered part of this invention.
Claims
1. A method for preparing adhesive articles by applying adhesive to one side, comprising the following steps: a. Apply a cleaning agent to at least one surface of a first substrate and dry the surface of the first substrate to which the cleaning agent has been applied; b. Apply an adhesive to at least one surface of a second substrate, and dry the surface of the second substrate to which the adhesive has been applied; and c. Bring the surface of the first substrate treated in step a and the surface of the second substrate treated in step b into contact to obtain the adhesive article; The cleaning agent comprises a polar solvent and a terminal aminosilane coupling agent; the polar solvent has a boiling point not exceeding 135°C and is isocyanate-free; the terminal aminosilane coupling agent conforms to the general formula YR. 1 -Si-(CH3) n X 3-n , where R 1 It is an alkylene group having 1-20 carbon atoms, where n is 0 or 1, X is selected from -Cl, CH3O-, C2H5O-, (CH3)2CHO- and CH3OCH2CH2O-, and Y is selected from -NH2 and -NHR. 2 R 2 The cleaning agent is an alkyl group having 1-10 carbon atoms; the concentration of the cleaning agent is 0.2%-1.2%; the second substrate is pretreated with a treatment agent comprising a halide and an organic solvent with a polarity greater than 2.4, and the concentration of the treatment agent is 1%-3%. The organic solvent with a polarity greater than 2.4 is one or more of the following: ethyl acetate, butyl acetate, butanone, and acetone.
2. The method as described in claim 1, characterized in that, The polar solvent is one or more of acetone, methyl ethyl ketone, ethyl acetate or butyl acetate, a mixture of butyl acetate and cyclohexane and methyl ethyl ketone, a mixture of methyl ethyl ketone and propylene glycol diacetate, or a mixture of butyl acetate and methyl ethyl ketone and propylene glycol methyl ether acetate.
3. The method as described in claim 1, characterized in that, The polar solvent is selected from methyl ethyl ketone, butyl acetate, a mixture of methyl ethyl ketone and ethyl acetate, a mixture of methyl ethyl ketone and butyl acetate, a mixture of methyl ethyl ketone and propylene glycol diacetate, a mixture of acetone and butyl acetate, a mixture of ethyl acetate and butyl acetate, a mixture of ethyl acetate, butyl acetate and methyl ethyl ketone, a mixture of butyl acetate, cyclohexane and methyl ethyl ketone, and a mixture of butyl acetate, methyl ethyl ketone and propylene glycol methyl ether acetate.
4. The method as described in claim 1, characterized in that, The polar solvent is methyl ethyl ketone.
5. The method as described in claim 1, characterized in that, The R 2 It is an alkyl group having 1-6 carbon atoms.
6. The method as described in claim 1, characterized in that, The R 2 It is an alkyl group having 1-4 carbon atoms.
7. The method as described in claim 1, characterized in that, The terminal aminosilane coupling agent is one or more of the following: γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and bis-(γ-trimethoxysilylpropyl)amine.
8. The method as described in claim 1, characterized in that, The concentration of the cleaning agent is 0.3%-1.0%.
9. The method as described in claim 1, characterized in that, The cleaning agent contains methyl ethyl ketone and an amino-terminated silane coupling agent, and the cleaning agent concentration is 0.3%-1.0%.
10. The method as described in claim 1, characterized in that, The halide is trichloroisocyanuric acid.
11. The method as described in claim 1, characterized in that, The treatment agent contains trichloroisocyanuric acid and ethyl acetate, and the concentration of the treatment agent is 1%-3%.
12. An adhesive article prepared by the method according to any one of claims 1-11.
13. Use of the adhesive article according to claim 12 in footwear production.
Citation Information
Patent Citations
Activating agent and preparation method thereof
CN106316147A
Method for making shoes by conducting single-sided gluing through powdered adhesive
CN107802056A
Method used for improving anaerobic adhesive performance through treatment of bonding surfaces with silane coupling agent
CN108587495A
Molting adheresive of wet and hard polyamidester
CN1095399A
Process for preparing laminate, laminate produced by said process and application of said laminate in shoes production
CN1098154C